Asthma in endurance swimming - Montjoy, M. (FINA World Sports Medicine Congress, 18, 2016)
Dr. Margo Mountjoy, McMaster University (CAN), talks about "Asthma in Endurance Swimming" at the FINA World Sports Medicine Congress 2016 (12:46 min).